2007
DOI: 10.1002/bmc.785
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatographic–electrospray tandem mass spectrometric determination of bisoprolol in human plasma

Abstract: An analytical method for the determination of bisoprolol in human plasma has been developed based on liquid chromatography-tandem mass spectrometry (LC-MS/MS). The analyte and internal standard (IS) diphenhydramine were cleaned up by protein precipitation with acetonitrile, reconstituted in mobile phase and separated by reversed-phase high-performance liquid chromatography (HPLC) using methanol:10 mm ammonium acetate:formic acid (70:30:0.1 v/v/v) as mobile phase. Detection was carried out by multiple reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Several chromatographic methods have been reported for the analysis of either BISO or HCTZ alone in human plasma; such methods have included HPLC coupled with UV [5][6][7] or fluorescence [8], diode array [9], LC-MS [10][11][12] or with tandem LC-MS/MS detection [13][14][15][16][17][18][19].…”
Section: Biso 1-[4-[[2-(1-methylethoxy)ethoxy]methyl]phenoxy]-3-mentioning
confidence: 99%
“…Several chromatographic methods have been reported for the analysis of either BISO or HCTZ alone in human plasma; such methods have included HPLC coupled with UV [5][6][7] or fluorescence [8], diode array [9], LC-MS [10][11][12] or with tandem LC-MS/MS detection [13][14][15][16][17][18][19].…”
Section: Biso 1-[4-[[2-(1-methylethoxy)ethoxy]methyl]phenoxy]-3-mentioning
confidence: 99%
“…Also, Liu et al [7] reported an accuracy ranged from 89.4%–113%, employing a precipitation with acetonitrile procedure for plasma sample preparations.…”
Section: Resultsmentioning
confidence: 99%
“…Bisoprolol was also separated from the proteins in human plasma by protein precipitation with acetonitrile, then analyzed by liquid chromatography coupled with mass spectrometry using diphenhydramine as internal standard. This technique applied for biological sample preparation provided a good recovery of the analyte, with values of 92.7±8.1, 94.8±4.9 and 95.9±3% at concentration of 1, 10 and 80 ng/mL [12]. Protein precipitation technique was applied for the separation of bisoprolol in human plasma, with a recovery rate of about 94.03, 100.3 and 96.29% for 1.5, 40 and 80 ng/mL of bisoprolol, respectively.…”
Section: Protein Precipitation Techniquementioning
confidence: 96%
“…These methods include liquid chromatography coupled with mass spectrometry (LC-MS/MS) [7][8][9][10][11][12][13][14][15][16][17], liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS/MS) [18,19], gas chromatography coupled with mass spectrometry (GC-MS) [3,[20][21][22], high performance liquid chromatography (HPLC) [23,24], high performance liquid chromatography coupled with mass spectrometry (HPLC-MS) [25,26], high performance liquid chromatography with fluorescence detection (HPLC-FLD) [2,27,28], high performance liquid chromatography coupled with ultraviolet detection (HPLC-UV) [29], reversed-phase ultra-high-performance liquid chromatography coupled with mass spectrometry (UHPLC-MS) [30].…”
Section: Introductionmentioning
confidence: 99%